PENGARUH SELF REGULATED LEARNING TERHADAP MINAT DAN HASIL BELAJAR SISWA MADRASAH IBTIDAIYAH - Ilma Fiveronica; Ika Ratih Sulistiani; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Self Regulated Learning has a great influence on students. Students who apply Self Regulated Learning tend to have their own learning motivation so that in the learning process it will be easier to understand the material. In addition, usually these students will think about learning objectives first in order to get maximum learning outcomes. This study aims to determine: 1) Self-Regulated Learning results on interest and learning outcomes at MI Roudlotun Nasyi'in; 2) The effect of Self Regulated Learning on students' interest in learning at MI Roudlotun Nasyi'in; 3) The effect of Self Regulated Learning on student learning outcomes at MI Roudlotun Nasyi'in. To achieve this goal, the researchers conducted research with quantitative research using survey methods by distributing questionnaires containing 10 questions to 45 students consisting of grades 4,5 and 6. The research location was at MI Roudlotun Nasyi'in Singosari. The results showed that more than 77% of students had applied the independent learning model. The result of the MANOVA test is that there is no influence between Self Regulated Learning and interest in learning, but the results of the questionnaire show that there is an influence between Self Regulated Learning and interest in learning. The results of the MANOVA test also answered that there was an influence between Self-Regulated Learning and learning outcomes.